Kurangnya Sex Education Karena Persepsi-Persepsi Negatif Di Lingkup Masyarakat - Supit, Elshaday; Pantow, Anssy; Karamoy, Pingkan; Y Aditama, Mint Husen (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This journal was created to find out whether in this day and age discussing sex is still a taboo subject for some people. This study aims to see whether talking about sex in society is still classified as sensitive and whether teenagers receive sex education while at school. And from the results of this study it was found that there wasstill a lack of sex education received by children (adolescents). The research that we conducted using the observation method, the interviews that were obtained in the field, the fact that discussing sexual matters is still a negative thing in the environment. The purpose of this study is to provide information and understanding of sex education in the community who have negative perceptions of the importance of sex education from parents, children, individuals and groups